The Significance of Enabling Human Consideration in Policymaking: How to Get the E-Ferry That You Want - Berntsen, Alexander; Sæther, Simen; Røyrvik, Jens; Biresselioglu, Mehmet Efe; Demir, Muhittin Hakan (Frontiers in Psychology, 2021)
There is broad agreement in literature and policy that the transport sector needs to switch to as much electric mobility as possible, in order to lower both energy consumption and greenhouse gas emissions. This transformation has required a high degree of technological innovation, and will likely continue to do so. Consequently, policymakers are striving to reward innovation in procurement tender contracts, in order to achieve sustainable innovation. At the same time, such contracts are often designed with a principle of technology neutrality in mind, to prevent any distortion of the market logic. This article suggests that it is misguided to try to perfect the logic of the tender system. Articulating a contract that rewards innovation is not a guarantee of a sustainable solution. The problem is not technological—it is moral: the mounting environmental challenge. Policymakers thus have clear ideas about what they want based on what they, through moral conviction, hold to be the right thing to do. We demonstrate through a case study—conducted as a part of the EU-funded ECHOES project under Work Package 6—on the electrification of the Flakk-Rørvik ferry connection, how policymakers were able to get what they want, in this case an e-ferry, and not a biodiesel ferry, despite of rather than because of the tender system logic: through thoroughly involving stakeholders who engage in continuous and frequent dialogue. The project stakeholders were able to meddle with the tender system logic, thereby ensuring that human considerations could overrule system logic as necessary. We argue that this project was a success because human judgement was in the driver's seat, not system logic. We by extension argue that systems will only help policymakers rise to moral issues by virtue of their potential for meddling.